The Power of Social Media in Influencing Customer Decision - Indrianty Sudirman (Magister Management, Hasanuddin University, 2020)
Social media currently plays a very important role as a process of communication and interaction between humans that is not limited by time and space. It is also used as a promotional media by companies to introduce their products to consumers. Many Muslim brands cosmetics also use social media and brand equity to attract consumer interest. This research was conducted on Muslim brand users in Makassar, who were dominated by women with an age range of 20-22 years who were students. The results showed that social media marketing and brand equity had a positive and significant effect on Muslim Cosmetic Brand cosmetics purchasing decisions in Makassar. Marketing online using social media has successfully built brand equity, which in turn affects the buying decision.